Pengaruh Disiplin dan Fasilitas Kerja terhadap Motivasi yang Berimplikasikan pada Kinerja Pegawai di Kecamatan Danau Teluk Kota Jambi - Khodijah, Ratumas; Bukit, Pantun; Hapsara, Osrita (Universitas Batanghari, 2024)
The aim of this research is to describe the discipline, work facilities, motivation and performance of employees in Danau Teluk District, Jambi City and to analyze the partial and simultaneous direct and indirect influence of discipline and work facilities on employee motivation and performance, as well as to analyze motivation on employee performance. To answer the research objectives, this research is supported by theoretical studies related to research variables, namely discipline, work facilities, motivation and performance. Apart from that, the author also looked for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this research are employees in Danau Teluk District, Jambi City, totaling 53 employees with conditions in 2022. The data analysis technique used in this research is through path analysis followed by hypothesis testing through the F test (Simultaneous) and t test (Partial). From the path analysis tests carried out, it was found that discipline and work facilities had an influence on motivation by 65.4% while the rest was influenced by other variables. Discipline and work facilities have an influence of 42.0% on employee performance in Danau Teluk District, Jambi City. This research concluded that discipline, work facilities, motivation and employee performance were in good and high condition. Apart from that, discipline and work facilities partially and simultaneously have a positive and significant influence on the motivation and performance of employees in Danau Teluk District, Jambi City. Likewise, motivation has a positive and significant influence on employee performance.